Treatment of Influenza A (H1N1) Virus Infections in Mice and Ferrets with Cyanovirin-N - Smee, Donald F. (2008)
Cyanovirin-N (CV-N), a protein derived from Nostoc ellipsosporum, neutralizes influenza virus infectivity by binding to specific high-mannose oligosaccharides (oligomannose-8 and -9) at glycosylation sites on the viral hemagglutinin HA1 subunit. Mouse-adapted viruses lose sensitivity to CV-N due to HA1 mutations that eliminate these glycosylation sites. Recently we created a hybrid (reassortant) influenza A/WSN/33 (H1N1) virus containing the HA gene of A/New Caledonia/20/99 (H1N1) with an Asp225Gly mutation in the HA1, that was lethal to mice yet retained sensitivity to CV-N. We then utilized this model system to test the efficacy of CV-N against influenza. CV-N efficacy was dose-responsive from 0.0625 to 1 mg/kg/day when administered intranasally twice daily for 4 days starting 4 h prior to virus exposure. In a second study, survival benefit was seen with CV-N treatments (0.5 mg/kg/day for 4 days) beginning at −4 or +6 hours, but was significantly reduced at +12 hours. The early treatment resulted in up to 100% survival and 1,000-fold reduction in lung virus titer on day 3 of the infection. In contrast, ribavirin (a positive control − 75 mg/kg/day) treatment resulted in 30% survival and 30-fold decrease in lung virus titers. Lung consolidation scores and lung weights were significantly reduced by CV-N and ribavirin treatment on day 6 of the infection. Ferrets infected with a non-animal adapted influenza A/Charlottesville/31/95 (H1N1) virus were treated intranasally with CV-N (50 μg twice daily for 5 days starting 24 h before virus challenge). They exhibited 100-fold lower viral titers in nasal washes than placebos 1 day after treatment, but virus titers were equivalent on days 2–7. CV-N has the potential for prophylaxis and early initiation of treatment of influenza virus infections.